Documentation and Phytochemical Screening of Most Commonly used Nutri-Medicinal Plants by Pregnant Women in Kyeizooba, Bushenyi District, Western Uganda - Catherine, Kiconco; Mugisha, Kamatenesi Maud; Bright, Waswa; Ogwang, Patrick Engeu; Kahwa, Ivan (Journal of Pharmacognosy & Natural Products, 2020)
Nutri-medicinal plants are widely used as a remedy for some ailments among pregnant women worldwide. There are different medicinal plants used by pregnant women in Uganda depending on the culture and knowledge of these medicinal plants. A cross sectional study was carried out on 135 women in Kyeizooba sub county Bushenyi District from September 2016 to March 2017. Medicinal plants used by pregnant women were identified and documented, and phytochemical screening of the frequently used nutri-medicinal plants was done and their effects were studied comparing with the available literature. Fidelity levels, Informant consensus factor and use values were used to obtain the most frequently used medicinal plants. Lamiaceae and Asteraceae families presented the highest number of medicinal plants used by pregnant women. The phytochemicals analyzed in the herbs were saponins, alkaloids, flavonoids, reducing compounds, phenols and steroids which were found to exist in some nutri-medicinal plants with varying intensities. Herbal medicines contain important phytochemicals which if standardized and the dosages prescribed could present therapeutic advantages to the users.
Keywords: Pregnancy; Traditional birth attendants; Nutri-medicinal plants; Phytochemicals